AGEING GRACEFULLY WITH CLEAR HEARING : A Journey to Lifelong Wellness - Dayang Suhana, Abang Madzhi (UNIMAS Publisher, 2025)
Ageing gracefully requires more than just keeping physical attractiveness; it also includes sustaining quality of life, freedom, and connection to the world. One frequently ignored yet critical part of this procedure is clear hearing. Hearing is essential for communication, mental well-being, and safety, making it an essential component of good ageing